Pengembangan Tong Berhitung Dalam Meningkatkan Pemahaman Konsep Materi Penjumlahan Dan Pengurangan - Maula, Dwi Inayatul; Zuliana, Eka; Kuryanto, Mohammad Syaffruddin (PGSD Universitas Muria Kudus, 2025)
The purpose of this study is to find out the results of the validity, effectiveness, and practicality test of the results of the development of Tong Counting learning media on the addition and subtraction material of grade II elementary school students. This development research uses the R&D (Research and Development) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The data analysis in this study uses quantitative analysis and qualitative analysis. The data analysis technique in this study uses quantitative descriptive analysis techniques. The results of the validity test by 2 validators in the media aspect obtained a score of 94.32% included in the